The role of individual differences in resistance to persuasion on memory for political advertisements - Miller, Stuart S.; Hutson, John P.; Strain, Megan L.; Smith, Tim J.; Palavamäki, Maria; Loschky, Lester C.; Saucier, Donald A. (Frontiers in Psychology, 2023)
When people see political advertisements on a polarized issue they take a stance on, what factors influence how they respond to and remember the adverts contents? Across three studies, we tested competing hypotheses about how individual differences in social vigilantism (i.e., attitude superiority) and need for cognition relate to intentions to resist attitude change and memory for political advertisements concerning abortion. In Experiments 1 and 2, we examined participants' intentions to use resistance strategies to preserve their pre-existing attitudes about abortion, by either engaging against opposing opinions or disengaging from them. In Experiment 3, we examined participants' memory for information about both sides of the controversy presented in political advertisements. Our results suggest higher levels of social vigilantism are related to greater intentions to counterargue and better memory for attitude-incongruent information.These findings extend our understanding of individual differences in how people process and respond to controversial social and political discourse.